Deletion of PIN4 Suppresses the Protein Transport Defects Caused by sec12-4 Mutation in Saccharomyces cerevisiae - Murakami-Sekimata, Akiko; Sekimata, Masayuki; Sato, Natsumi; Hayasaka, Yuto; Nakano, Akihiko (Microbial Physiology, 2020)
Newly synthesized secretory proteins are released into the lumen of the endoplasmic reticulum (ER). The secretory proteins are surrounded by coat protein complex II (COPII) vesicles, and transported from the ER and reach their destinations through the Golgi apparatus. Sec12p is a guanine nucleotide exchange factor for Sar1p, which initiates COPII vesicle budding from the ER. The activation of Sar1p by Sec12p and the subsequent COPII coat assembly have been well characterized, but the events that take place upstream of Sec12p remain unclear. In this study, we isolated the novel extragenic suppressor of sec12-4, PIN4/MDT1, a cell cycle checkpoint target. A yeast two-hybrid screening was used to identify Pin4/Mdt1p as a binding partner of the casein kinase I isoform Hrr25p, which we have previously identified as a modulator of Sec12p function. Deletion of PIN4 suppressed both defects of temperature-sensitive growth and the partial protein transport observed in sec12-4 mutants. The results of this study suggest that Pin4p provides novel aspects of Sec12p modulations.